2016
DOI: 10.1016/j.ajhg.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in MME, Encoding Metalloprotease Neprilysin, Are Linked to Late-Onset Autosomal-Dominant Axonal Polyneuropathies

Abstract: Axonal polyneuropathies are a frequent cause of progressive disability in the elderly. Common etiologies comprise diabetes mellitus, paraproteinaemia, and inflammatory disorders, but often the underlying causes remain elusive. Late-onset axonal Charcot-Marie-Tooth neuropathy (CMT2) is an autosomal-dominantly inherited condition that manifests in the second half of life and is genetically largely unexplained. We assumed age-dependent penetrance of mutations in a so far unknown gene causing late-onset CMT2. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 59 publications
5
56
0
2
Order By: Relevance
“…Conversely, three out of the 17 mutations detected in this study (p.Trp24*, p.Pro156Leufs*14 and p.Arg448*) were described previously in European and American patients, and linked to late-onset AD polyneuropathies 8. In our cohort, the healthy relatives carrying the heterozygous LoF mutations (such as, p.Pro156Leufs*14, p.Arg448* and p.Trp750Glyfs*24), who were older than the affected individuals, did not present any signs of neuropathy.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Conversely, three out of the 17 mutations detected in this study (p.Trp24*, p.Pro156Leufs*14 and p.Arg448*) were described previously in European and American patients, and linked to late-onset AD polyneuropathies 8. In our cohort, the healthy relatives carrying the heterozygous LoF mutations (such as, p.Pro156Leufs*14, p.Arg448* and p.Trp750Glyfs*24), who were older than the affected individuals, did not present any signs of neuropathy.…”
Section: Discussionsupporting
confidence: 47%
“…The Neprilysin (NEP) protein is expressed in many tissues,14 including the PNS and central nervous system (CNS),15 16 although NEP-deficient mice do not show any obvious abnormalities in motor performance or degeneration of their peripheral nerves 8. Neurodegeneration in a length-dependent neuropathy may not be so evident in a mouse model given their short life span and the reduced vulnerability of shorter axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MME c.674G > C (p.G225A) missense variant was absent in our unaffected controls, but it is represented at low frequency in public control datasets (MAF = 0.02%); although the prevalence of primary headache in public datasets is unknown, this could reflect incomplete penetrance and the interaction with other genetic or environmental factors. Furthermore, rare loss-of-function and missense MME variants were recently associated to late onset dominant axonal polyneuropathies (Charcot-Marie-Tooth Neuropathy Type 2, CMT2; spinocerebellar ataxia with neuropathy, SCA43) [38, 39] and to a rare autosomal recessive variant of CMT2 [40]; none of the neuropathy patients described in these studies was reported to have migraine or CH symptoms, however individuals with MME mutations were reported to experience painful sensations [38]. Given the variety of NEP target peptides and their wide expression pattern, it is plausible that MME deleterious variants may contribute to the aetiology of different neurological conditions, and further studies are needed to identify the mechanisms underlying the phenotypic differences.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MTMR5 loss-of-function may be exacerbated in humans relative to mice, potentially explaining the greater reductions in myelinated axon numbers observed in patients (28,29). Although the precise cause of this feature is unclear, several mouse models of axonal CMT have shown phenotypes milder than their corresponding human conditions (36,(44)(45)(46)(47)(48). Incomplete radial sorting can be caused by defects in both axons and Schwann cells (1,49).…”
Section: Mtmr5-deficient Mice As a Model Cmt Diseasementioning
confidence: 99%